A fuzzy neural network approximator with fast terminal sliding mode and its applications - Shuanghe Yu; Xinghuo Yu; Zhihong Man (ICONIP '02 : proceedings of the 9th International Conference on Neural Information Processing : computational intelligence for the E-age : November 18-22, 2002, Singapore, 2002)
This paper presents a novel training method for fuzzy neural network (FNN) systems to approximate unknown nonlinear continuous functions. The training algorithm uses the principle of the fast terminal sliding mode (TSM) into the conventional gradient descent (GD) learning algorithm. It guarantees that the approximation is stable and converges to the optimal approximation function with improved speed. The proposed FNN approximator is then applied in the control of an unstable nonlinear system and the Duffing system. The simulation results demonstrate the effectiveness of the proposed method.